Perlindungan Konsumen terhadap Fintech Lending dan Penagihan Tidak Etis - Fiqhi Dzahabi; Edo Nugraha; Helfira Citra (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
The rapid advancement of information technology has significantly transformed global civilization, including the financial sector through the emergence of Financial Technology (fintech). One of the most widely used forms of fintech in Indonesia is Peer-to-Peer (P2P) Lending, which offers easy access to financing without collateral through digital platforms. However, this rapid growth has also raised new challenges, particularly regarding consumer protection. This study employs a normative juridical approach with descriptive-analytical specifications to examine the legal framework for consumer protection in P2P Lending services. The findings reveal that although the Electronic Information and Transactions Law (ITE Law) does not explicitly regulate fintech lending, various regulations such as OJK Regulation No. 77/2016, No. 13/2018, and No. 06/2022 provide legal protection through both preventive and repressive measures. Furthermore, the enforcement of administrative and criminal sanctions against illegal fintech operators is essential, along with the reinforcement of the principle of good faith in debt collection practices. Thus, a more comprehensive and stringent regulatory framework is needed to ensure legal protection, personal data security, and consumer confidence in P2P Lending services.